For True Humanity: Harmonization of Islamic Law and Human Rights Towards Universal Justice - Karimullah, Suud Sarim (Matan : Journal of Islam and Muslim Society, 2023)
This study aims to analyze the challenges and potentials in harmonizing Islamic law and human rights to achieve universal justice. The research method used is library research with a descriptive-analytical approach. Literature analysis was conducted to understand Islamic law and human rights concepts and principles, as well as the challenges and opportunities associated with harmonizing the two. The results show that harmonizing Islamic law and human rights can contribute significantly to achieving universal justice. This harmonization requires an awareness of the importance of protecting individual rights and universal justice and recognizing internationally recognized human rights principles. In Indonesia, a country with a majority Muslim population, harmonization between Islamic law and human rights must be done by considering the high religious and cultural diversity. There needs to be contextualization efforts with national legal systems and policies that support protecting individual rights fairly and inclusively. The role of state institutions, such as courts, legislatures, and law enforcement agencies, is also essential in encouraging the implementation of harmonization in line with the principles of universal justice.